Possibilities for adjuvant treatment in colon cancer - Stec, Rafał; Bodnar, Lubomir; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2009)
Each year almost a million patients receive a diagnosis of colorectal cancer and it is the cause of death of half a million patients. Approximately 13 000 new cases are diagnosed each year in Poland. Almost 230 000 patients are candidates for adjuvant chemotherapy following surgery yearly. The age of first diagnosis of CRC is 40 years, but rapidly increases from 50 years. CRC was reported to be the most common cancer in Poland in patients who were ł 65 years (62% in male and 66% in female of all cases of CRC). The proportions of deaths ł 65 years are 70% in males and 77% in females. In adjuvant therapy of colon cancer are used: LF (leucovorin and 5-Fu), capecitabine and FOLFOX (oxaliplatin and 5-Fu and leucovorin). In stage II of the TNM scale adjuvant chemotherapy can be used for patients with high-risk factors after individual analysis and based on only the LF schedule. Based on clinical trials, in stage III of the TNM scale FOLFOX should be used for optimal adjuvant chemotherapy of colon cancer. In case of intolerance of the FOLFOX schedule, capecitabine or the LF schedule can be considered.